Assessment of the mechanical performance of recycled unbound materials for pavement subbase layers - Grégoire, C (2015)
The cyclic load triaxial test is a laboratory test that allows studying the mechanical behaviour of unbound granular materials used in base/subbase layers of road pavements. The resilient modulus and permanent strains are required as inputs in structural pavement design. This paper presents some results obtained for recycled materials (crushed concrete aggregate and blended crushed waste aggregate), with a view to promoting their use in pavement structures. Results relating to a reference material (limestone) are also presented, for comparison. All the test results discussed in this paper were obtained in variable cyclic radial pressure (VCP) tests. The tests performed (VCP) aim to study the influence of water content on the resilient modulus of recycled materials, as well as on the resistance to permanent deformation. Using the experimental data as a basis, further modelling work was carried out to establish the stresses developing in base/capping layers in typical Belgian road pavements. These numerical results allow to propose some simplifications of the stress paths applied in the testing procedures and to establish a new test protocol that also considers compaction during construction works. The results of this research work provide an excellent set of findings for the mechanical characterization of unbound base materials through the cyclic triaxial test, and contribute to a better understanding and correct application of recycled materials under geotechnical engineering background